A small principle of charity. Memory and devotion in the testament of Maria Dávila (1441-1511) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2020)
The aim of this article is to discuss the final days of María Dávila (1450-1511), woman of the oligarchy of Ávila, lady of the royal circle, widow, and nun. As other prestigious families of her time, the Ávila family built spiritual, parental, and patron-client bonds and took over significant hierarchy roles of the Catholic Monarchy. The social figures that juxtapose in the historical identity of María can be thought as notable testimonies to understand how in the Late Middle Ages there were women capable of managing patrimonies, financing religious institutions, doing charity work, and leading the fate of entire families. In this investigation, we will use the Archives of the Monastery ‘Las Gordillas’, and Maria Davila’s will as mainly sources.
Keywords: Testaments; Women; Nobility; Patronage; Charity